2013
DOI: 10.1021/mp400087y
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo Characterization of Particle Transport in Mucus Secretions Coating Freshly Excised Mucosal Tissues

Abstract: Sustained drug delivery to mucosal surfaces has the potential to improve the effectiveness of prophylactic and therapeutic treatments for numerous diseases and conditions, including inflammatory bowel disease, sexually transmitted diseases, cystic fibrosis, glaucoma, dry eye and various cancers. Sustained delivery systems such as nanoparticles can be useful for mucosal delivery, but recent work suggests they should penetrate the rapidly cleared mucus barrier that overlies all mucosal epithelia to achieve unifo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 42 publications
5
63
0
Order By: Relevance
“…Consider the heterogeneity of mucus pore sizes 40 , we have also constructed a model system composed of cross-linked polymer network with random pore size (See Methods for details) to represent mucin fibers, as shown in Fig. 7a.…”
Section: Acs Paragon Plus Environment Nano Lettersmentioning
confidence: 99%
“…Consider the heterogeneity of mucus pore sizes 40 , we have also constructed a model system composed of cross-linked polymer network with random pore size (See Methods for details) to represent mucin fibers, as shown in Fig. 7a.…”
Section: Acs Paragon Plus Environment Nano Lettersmentioning
confidence: 99%
“…different mucosal surfaces from mice was investigated and compared. The particles were mucus-penetrating, and as they were assumed not to interact with the mucus, the study illustrated the steric barrier of mucus [17]. It was found that the diffusion of 100 nm particles was more restricted in colonic and tracheal tissue than in the small intestinal mucosal tissue, whereas the diffusion was least restricted in oestrus-phase vaginal tissue [17].…”
Section: Mucus Function and Compositionmentioning
confidence: 94%
“…Human mucus is usually isolated from the female genital tract or as sputum from patients with cystic fibrosis. However, it is important to be aware of possible implications related to the mucus source, for example the varying viscosity of cervicovaginal mucus during the oestrous cycle [17] or the abnormal high DNA content and viscosity of cystic fibrosis sputum [6]. Animal mucus can be obtained from all mucosal sites and is usually isolated from larger animals as pigs and horses to obtain adequate quantities.…”
Section: Mimicking the Mucus Barriermentioning
confidence: 99%
“…The main bronchi then bi-and also trifurcate into smaller bronchi and bronchioles, until the terminal bronchioles appear to show sac-like structures (approximately generation [16][17]. With these so-called respiratory bronchioles begins the gas-exchanging respiratory zone (generation [17][18][19][20][21][22][23], which mainly comprises the alveolar ducts and alveolar sacs (i.e. alveoli; approximately 500 million per adult lung).…”
Section: Morphology Of the Human Lungsmentioning
confidence: 99%
“…Whereas the cross-sectional surface of the airways (generation 0-16) is only a few square meters, the surface area increases exponentially in the alveolar region (generation [17][18][19][20][21][22][23] to about 75-140 m 2 [ 8 ]. Via the conducting zone, the inspired air is rapidly transported from the central to the peripheral lung by turbulent and laminar fl ow, while it is decelerated to diffusive movement in the transition to the respiratory zone to facilitate the gas exchange [ 9 ].…”
Section: Morphology Of the Human Lungsmentioning
confidence: 99%